INOVASI MANAJEMEN SDM UNTUK MENDUKUNG SMART GOVERNANCE DI KECAMATAN CIBINONG CIANJUR SELATAN - Undang; Nugraha, Anggi; Lismawan, Adrian (Sawala Cendikia : Jurnal Penelitian Multidisiplin, 2026)
This study aims to analyze the influence of Human Resource Management (HRM) innovation on the implementation of smart governance and its impact on community satisfaction in Cibinong Subdistrict, South Cianjur. The background of this research highlights the gap between the demands of digital transformation and the limitations of infrastructure and human resource capacity at the local government level. Using a quantitative approach through Structural Equation Modeling (SEM-PLS) with 150 respondents, this study examines causal relationships among the variables. The results indicate that HRM innovation has a very strong and significant effect on smart governance, with a path coefficient of 0.978. Furthermore, HRM innovation and the implementation of smart governance each have a direct positive effect on community satisfaction. Another important finding shows that smart governance acts as a partial mediating variable that strengthens the influence of HR innovation in improving public service quality. The development of digital competencies, an innovation culture, and collaborative leadership are proven to be key factors in overcoming bureaucratic barriers. In conclusion, strengthening innovative human resource capacity is crucial for realizing transparent, efficient, and responsive governance to enhance public trust at the subdistrict level.